2021
DOI: 10.1080/23279095.2021.1973471
|View full text |Cite
|
Sign up to set email alerts
|

Systematic administration and analysis of verbal fluency tasks: Preliminary evidence for reliable exploration of processes underlying task performance

Abstract: Verbal fluency (VF) tasks are typically scored by the number of acceptable words generated within an allotted time (i.e., total score). However, total scores do not provide insight into verbal and executive processes underlying VF task performance. Further analyses have been implemented to increase the analytical power of VF tasks, but systematic scoring guidelines are needed. We generated instructions for administration, scoring, and analyses of total scores, errors, temporal parameters, clustering, and switc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…For example, Tröger et al (2019) reported a significant difference between groups on an animal fluency task where IwDs switched significantly less than MCI and CHOA groups (IwDs < MCI = CHOA), highlighting the different cognitive characteristics of CHOAs and IwDs. Switching is considered to be a more cognitively demanding skill than clustering, as it involves “higher cognitive functions, such as cognitive flexibility and strategic search processes” ( Lehtinen et al, 2021 , p. 3). Troyer et al (1998) reported that participants with frontal lobe lesions demonstrated less switching than healthy controls, indicating that executive functioning difficulties could be a factor in the decreased performance on verbal fluency tasks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Tröger et al (2019) reported a significant difference between groups on an animal fluency task where IwDs switched significantly less than MCI and CHOA groups (IwDs < MCI = CHOA), highlighting the different cognitive characteristics of CHOAs and IwDs. Switching is considered to be a more cognitively demanding skill than clustering, as it involves “higher cognitive functions, such as cognitive flexibility and strategic search processes” ( Lehtinen et al, 2021 , p. 3). Troyer et al (1998) reported that participants with frontal lobe lesions demonstrated less switching than healthy controls, indicating that executive functioning difficulties could be a factor in the decreased performance on verbal fluency tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Both methods used a task congruent method to cluster responses. A task congruent method of clustering includes clustering either semantically related words for a category fluency task (i.e., verb fluency or animal fluency) or phoneme-relatedness criteria for letter fluency tasks ( Lehtinen et al, 2021 ). The objective clustering method utilized the Lancaster Norms database ( Lynott et al, 2020 ) to analyze clusters and switches.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of correct items were counted. Intrusions, repetitions, proper names, paraphasias (the meaning of the word is unclear) and grammatical variations were not accepted (See Lehtinen et al, 2021).…”
Section: Semantic Verbal Fluency Tasksmentioning
confidence: 99%
“…PVF tests usually include 3 trials (with 3 different starting letters) (Lehtinen et al, 2021). The starting letters in PVF have a significant effect, as they determine the number and frequency of the eligible words (Strauss et al, 2006).…”
Section: Types and Characterizationmentioning
confidence: 99%